Immune Checkpoint Targets for Host-Directed Therapy to Prevent and Treat Leishmaniasis - Kumar, Rajiv; Chauhan, Shashi Bhushan; Ng, Susanna S.; Sundar, Shyam; Engwerda, Christian R. (Frontiers in Immunology, 2017)
Leishmaniasis encompasses a group of diseases caused by protozoan parasites belonging to the genus Leishmania. These diseases range from life threatening visceral forms to self-healing cutaneous lesions, and each disease manifestations can progress to complications involving dissemination of parasites to skin or mucosal tissue. A feature of leishmaniasis is the key role host immune responses, and in particular, T cells, play in disease onset and progression. This ranges from the development potent regulatory T cell responses that suppress anti-parasitic immunity to hyper-activated CD8+ T cells that cause serious damage to host tissue. There is no licensed human vaccine and drug treatment options are often limited and problematic. Hence, there is an urgent need for new strategies to improve the efficacy of current vaccine candidates and/or enhance both anti-parasitic drug effectiveness and subsequent immunity in treated individuals. Here, we describe our current understanding about host immune responses contributing to disease protection and progression in the various forms of leishmaniasis. We also discuss how this knowledge may be used to develop new strategies for host-directed immune therapy to prevent or treat leishmaniasis. Given the major advances made in immune therapy in the cancer and autoimmune fields in recent years, there are significant opportunities to ride on the back of these successes in the infectious disease domain. Conversely, the rapid progress in our understanding about host immune responses during leishmaniasis is also providing opportunities to develop novel immunotherapy strategies that could have broad applications in diseases characterised by inflammation or immune dysfunction.